2020
DOI: 10.3389/fvets.2020.00434
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography (CT)-Assisted 3D Cephalometry in Horses: Interincisal Angulation of Clinical Crowns

Abstract: The angle encompassed between opposing incisors in horses is assumed to decline with age. Previous studies merely consider the overall profile view of clinical crowns presuming a generalized angle, neglecting potential tooth position-dependent differences. Cephalometric measurements from 3D computed tomographic thick-slab reconstructions of single incisors within a global reference frame were used to determine clinical crown interincisal angulation (IIA) of 48 horses. Based on predefined dentoalveolar landmark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Previous research has shown that horses 8 to 15 years of age typically have IIA of approximately 90°, which is consistent with the SEAR findings in the current study. 14,15 With the mean age of the TB group (7.47 years) being significantly younger than the mean age of the SEAR group (10.4 years), it is logical to assume that this difference in age could explain the difference in IIA between the 2 breeds. However, it is interesting to note that although it is widely accepted that IIA decreases with age, the results of the current study did not find age to have a significant effect on IIA ( P = 0.12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that horses 8 to 15 years of age typically have IIA of approximately 90°, which is consistent with the SEAR findings in the current study. 14,15 With the mean age of the TB group (7.47 years) being significantly younger than the mean age of the SEAR group (10.4 years), it is logical to assume that this difference in age could explain the difference in IIA between the 2 breeds. However, it is interesting to note that although it is widely accepted that IIA decreases with age, the results of the current study did not find age to have a significant effect on IIA ( P = 0.12).…”
Section: Discussionmentioning
confidence: 99%
“…1 A CT 3D cephalometric approach has also been investigated for the purpose of age determination in horses by measuring the angulation between incisor clinical crowns but has not been found to be a reliable tool for this purpose. 14…”
Section: Introductionmentioning
confidence: 99%
“…rotating movement in their alveoli. 28 However, there are no data on the distribution of masticatory forces within the incisor arcades.…”
Section: Discussionmentioning
confidence: 99%
“…A recent CT study demonstrated that opposing corner incisors have the highest annual angle decline, i.e. rotating movement in their alveoli 28 . However, there are no data on the distribution of masticatory forces within the incisor arcades.…”
Section: Discussionmentioning
confidence: 99%
“…Standing computed tomography (CT) of the head using a big bore sliding gantry (Somatom Sensation Open; Siemens Healthcare, Forchheim, Germany) was performed as previously described [ 37 , 38 ]. The radiological assessment, using Syngo imaging software (Siemens Healthcare), comprised three-dimensional volume rendering, multiplanar reconstructions, and orthogonal reconstructions.…”
Section: Case Presentationmentioning
confidence: 99%